2008
DOI: 10.2307/25148854
|View full text |Cite
|
Sign up to set email alerts
|

Internet Users' Information Privacy-Protective Responses: A Taxonomy and a Nomological Model

Abstract: Although Internet users are expected to respond in various ways to privacy threats from online companies, little attention has been paid so far to the complex nature of how users respond to these threats. This paper has two specific goals in its effort to fill this gap in the literature. The first, so that these outcomes can be systematically investigated, is to develop a taxonomy of information privacy-protective responses (IPPR). This taxonomy consists of six types of behavioral responses-refusal, misreprese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
287
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(320 citation statements)
references
References 78 publications
(145 reference statements)
8
287
0
4
Order By: Relevance
“…We argue that previous research focuses only on user choice to either withhold or release personal information. This decision is one component of user payoff, which we consider as "the degree to which a mobile user perceives as fair the benefits he or she receives in return for the release of personal information" [41] if user's payoff is not assured, data security is in peril [2].…”
Section: Introductionmentioning
confidence: 99%
“…We argue that previous research focuses only on user choice to either withhold or release personal information. This decision is one component of user payoff, which we consider as "the degree to which a mobile user perceives as fair the benefits he or she receives in return for the release of personal information" [41] if user's payoff is not assured, data security is in peril [2].…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, digital and networked society has new challenges with personal information privacy (Angst and Agarwal 2009;Malhotra et al 2004).Commercial websites seeking personal information online should disclose the way the data are collected, processed, and used (Hong and Thong, 2013).Firms use technologies such as customer relationship management to launch individually targeted marketing programs, and their information practice may conflict with the information privacy rights of customers (Son and Kim, 2008). Many Internet users are expected to adopt certain forms of behavior to protect information privacy.…”
Section: Concern For Information Privacymentioning
confidence: 99%
“…For example, found that individuals were more willing to self-disclose in online transactions when their general interests in the content surpassed general Internet privacy concerns. Likewise, Son and Kim (2008) noted that general privacy concerns might motivate privacy-protective responses, which could manifest in several behaviours, such as negative word-of-mouth, complaints to peers, and report to third parties.…”
Section: General Privacy Concerns and Transactional Privacy Concernsmentioning
confidence: 99%
“…First, past Information System (IS) research has substantially advanced our understanding of information privacy (e.g., Bélanger and Crossler 2011;Jiang et al 2013;Smith et al 2011). While IS literature has explored several aspects of information privacy, its primary focus has been on issues triggered by personal information collection (e.g., Malhotra et al 2004;Son and Kim 2008). As a result, to the best of our knowledge, there is limited research done to elucidate privacy issues associated with an extended scope of information collection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation